Effect of Mn Doping on Microstructure and Corrosion Behavior of CoCuNiTi High-Entropy Alloy Coatings - Mingxing Ma; Zhixin Wang; Chengjun Zhu; Ying Dong; Lixin Liu; Liang Zhao; Qingxue Cui; Dachuan Zhu; Deliang Zhang (Crystals)
Mn-doped CoCuNiTi HEACs were prepared on 45 carbon steel substrate by laser cladding. CoCuNiTi and CoCuMnNiTi HEACs are dual-phase structures composed of FCC and BCC. The addition of Mn causes a decrease in the lattice constant and cell volume of the above two phases, as well as an increase in the density of the two phases and the FCC phase content. The microstructures of the two alloys are the typical dendritic structures. Ti and Co elements are enriched in the dendrite region; Cu element is enriched in the interdendrite region; the distribution of Mn is the most uniform in the dendrite and interdendrite regions. The addition of Mn element causes the microstructure to be significantly refined, and the width of the primary dendrite is reduced from 8.10 μm to 4.11 μm. CoCuNiTi alloy belongs to activation dissolution, and the Mn-containing alloy exhibits an obvious passivation zone. The addition of Mn element increases the capacitive reactance arc radius and the maximum phase angle of the alloy, indicating that the corrosion resistance of the Mn-containing alloy is significantly improved.